Penerapan Hak-Hak Nelayan Buruh di Wilayah Pantai Muncar Banyuwangi - Safi'i, Nurul; Mochtar, Dewi Astutty; Ariyanti, Ariyanti (Postgraduate University of Merdeka Malang, 2023)
This article aims to examine and analyze the implementation of protection for fishing workers and the efforts that can be made by parties to improve the conditions of fishing workers in Muncar Banyuwangi, East Java, Indonesia. The method used in compiling this scientific article is the empirical legal research method. The types of data used are primary data and secondary data. Primary data was obtained by conducting interviews with ship owners and fishermen workers. The results show that regulatory protection for fishermen workers has been provided. With the existence of Law Number 31 of 2004 concerning Fisheries and the existence of Presidential Instruction Number 15 of 2011 concerning Fisherman Protection. And it is hoped that it will be even better with the promulgation of Law Number 7 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Farmers and Salt Farmers. However, the implementation of legal protection was not carried out due to a lack of intensive socialization of related parties and a lack of awareness of ship/boat owners and fishermen workers regarding safety equipment. Lack of awareness of ship/boat owners and labor fishermen in the Muncar coastal area of Banyuwangi district in providing safety equipment. This is because ship owners and fishermen workers think that disasters come from God, and when the time comes for a disaster, they will definitely suffer. Apart from that, the use of safety equipment is only a distraction when working fishermen are pulling nets, so most of the crew members or working fishermen are reluctant to use safety equipment. Given these obstacles, there is a need for outreach activities and legal action for boat owners who do not comply with the rules for using safety equipment.